Presence of deoxynivalenol in wheat milling products in Serbia during 2016-2017 - Jauković Marko M.; Zečević Veselinka M.; Stanković Slavica Ž.; Krnjaja Vesna S. (Zbornik Matice Srpske za Prirodne Nauke, 2017)
Deoxynivalenol (DON) is one of several mycotoxins produced by certain Fusarium species that frequently infect wheat, corn, rice, oats, barley and other grains in the field or during storage. DON affects animal and human health causing vomiting, acute temporary nausea, diarrhea, abdominal pain, headache, dizziness and fever. The objective of this study was to evaluate the natural occurrence of deoxynivalenol (DON) in white wheat flour, whole wheat flour and wheat bran. In this study, a total of 75 white wheat flour, whole wheat flour and wheat bran samples were collected in the period of 2016-2017. All samples were analyzed for DON by enzymelinked immunosorbent assay. DON was detected in 23 out of 45 white wheat flour samples (51.11%), at levels ranging from 99 μg/kg to 440 μg/kg. Out of 15 whole wheat flour samples, 14 were contaminated by DON (93.33%), at levels ranging from 98 μg/kg to 479 μg/kg. The maximum contamination level of DON (2,790 μg/kg) in this study was found in wheat bran. Presence of DON was detected in all 15 samples of wheat bran (100%). These results suggest a high percentage of contaminated samples, especially among wheat bran samples, which raises a risk for consumers of wheat bran and the need to monitor final products before consumption.